Dynamic Response of Steel Box Girder under Internal Blast Loading - Shujian Yao; Nan Zhao; Zhigang Jiang; Duo Zhang; Fangyun Lu (Advances in Civil Engineering)
This paper aims at investigating the dynamic response of the steel box girder under internal blast loads through experiments and numerical study. Two blast experiments of steel box models under internal explosion were conducted, and then, the numerical methods are introduced and validated. The dynamic response process and propagation of the internal shock wave of a steel box girder under internal blast loading were investigated. The results show that the propagation of the internal shock wave is very complicated. A multi-impact effect is observed since the shock waves are restricted by the box. In addition, the failure modes and the influence of blast position as well as explosive mass were discussed. The holistic failure mode is observed as local failure, and there are two failure modes for the steel box girder's components, large plastic deformation and rupture. The damage features are closely related to the explosive position, and the enhanced shock wave in the corner of the girder will cause severe damage. With the increasing TNT mass, the crack diameter and the deformation degree are all increased. The longitudinal stiffeners restrict the damage to develop in the transverse direction while increase the crack diameter along the stiffener direction.